Assessment of walkability and walkable routes of a 15-min city for heat adaptation: Development of a dynamic attenuation model of heat stress - Wang, Yu; He, Bao-Jie; Kang, Chong; Yan, Li; Chen, Xueke; Yin, Mingqiang; Liu, Xiao; Zhou, Tiejun (Frontiers in Public Health, 2022)
Actively addressing urban heat challenges is an urgent task for numerous cities. Existing studies have primarily developed heat mitigation strategies and analysed their cooling performance, while the adaptation strategies are far from comprehensive to protect citizens from heat-related illnesses and deaths. To address this research gap, this paper aims to enhance people’s adaptation capacity through investigating the walkability within the 15-min cities (FMC). Respecting thermal comfort, health and safety, this paper developed a dynamic attenuation model (DAM) of heat stress, with the consideration of heat stress aggravation, continuance, and alleviation. An indicator of remaining tolerant heat discomfort (Rt) was proposed, with the integration of Universal Thermal Climate Index (UTCI), to assess the heat-related walkability. With the empirical studies among 128 residents in Mianyang, China under four levels of heat stress, the maximum tolerant heat discomfort was determined to be 60 min^'. Furthermore, the DAM was applied to an FMC case with 12 neighbourhoods in Fucheng, Mianyang, China. The results indicate that for each neighbourhood, the street was generally walkable with a Rt ranging between 15 and 30 min^', after walking for 900 m. A population-based FMC walkability was further determined, finding that the core area of the FMC was favourable for walking with a Rt of 45-46 min^', and the perpetual areas was also walkable with a Rt of 15-30 min^'. Based on such results, suggestions on public services (e.g. frequently used, often used and occasionally used) planning were presented. Overall, this paper provides a theoretical model for the walkability analysis and generates meaningful implications for heat adaptation for resilient, safe comfortable and liveable FMC creation.